2020
DOI: 10.1302/2058-5241.5.190095
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic and open debridement in primary elbow osteoarthritis: a systematic review and meta-analysis

Abstract: Primary osteoarthritis (OA) of the elbow can cause disabling symptoms of pain, locking, stiffness, and a limitation in the range of motion. There is no consensus regarding the role of open and arthroscopic debridement in the treatment of symptomatic primary elbow OA. The aim of this study is to systematically review the outcome of surgical debridement. A preoperative/postoperative comparison will be made between the two surgical procedures. All studies reporting on debridement as treatment for primary elbow OA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 64 publications
1
4
0
Order By: Relevance
“… 13 Similarly, another review of 300 elbows in 292 patients undergoing open elbow release for PEOA showed a mean arc improvement of 29.4° ± 9.7 at a mean follow-up of 55 ± 20 months. 7 Our cohort achieved similar increases in arc of motion at just 3 months postoperatively, which represented 99% of the final arc of motion. This difference may be due to the increased granularity of our results, as the de Klerk et al study reported ROM at final follow-up and excluded studies with follow-up of fewer than 12 months.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“… 13 Similarly, another review of 300 elbows in 292 patients undergoing open elbow release for PEOA showed a mean arc improvement of 29.4° ± 9.7 at a mean follow-up of 55 ± 20 months. 7 Our cohort achieved similar increases in arc of motion at just 3 months postoperatively, which represented 99% of the final arc of motion. This difference may be due to the increased granularity of our results, as the de Klerk et al study reported ROM at final follow-up and excluded studies with follow-up of fewer than 12 months.…”
Section: Discussionsupporting
confidence: 55%
“…Open débridement, osteoplasty, and capsular release are common treatments for elbow stiffness and have been shown to provide durable benefit to patients with PEOA. 7 , 13 The main findings of our study were 1) the mean time to achieve the final arc of motion after elbow release was 3 months postoperatively, with 79% of patients achieving their final ROM arc by that time; 2) our cohort in total achieved 85% of their final arc at 2 weeks postoperatively, and 99% of their final arc at 3 months; 3) preoperative, intraoperative, and 2-week postoperative arc of motion do not correlate with the final arc of motion; and 4) there were no characteristics or thresholds of motion which conferred a higher likelihood of achieving a better result postoperatively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the range of flexion, which was in favor of the open group, the extension arc, pain score (visual analog scale), Mayo Elbow Performance Score, and radiological recurrence for the 2 groups were equivalent. However, a review by de Klerk et al 133 showed a complication rate of 12% after open debridement and 6% after arthroscopic debridement for primary elbow osteoarthritis. Besides arthroscopic treatment for radial head fractures or contracture release exist, so the preference between the open or arthroscopic approach for these procedures is currently unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In advanced OA, severe joint deformities will occur, rendering pharmacological treatment futile, and surgical treatment is the only option, most commonly with arthroscopic debridement and total joint replacement 61 . Arthroscopic debridement is indicated for mild to moderate OA and often provides a more satisfactory outcome 62 . Total joint replacement, on the other hand, is suitable for patients with severe OA and can not only significantly reduce pain, but also correct joint deformities and restore joint function, making it the last choice for all OA patients 63 .…”
Section: Physiopathology Of Osteoarthritismentioning
confidence: 99%